Description of Knowledge regarding the Application of Independent Isolation and the Application of the Covid-19 Protocol in the New Normal Era for Women of Fertile Age in Indonesia - Ida Rahmah Burhan; Abdiana Abdiana; Zurriyati Hanifa (Andalas Obstetrics And Gynecology Journal, 2021)
The purpose of this study is to describe the knowledge regarding the application of self isolation and the application of the Covid-19 protocol in the new normal era in women of childbearing age. This type of research is a descriptive study with a cross-sectional design. This research was conducted on 21-24 September 2020 via Google form. The study population was all women of childbearing age in Indonesia. The number of respondents was 1049 people. Data obtained using a validated questionnaire. Most of the respondents were aged over 15-31 years. The results showed that the knowledge of women of childbearing age regarding the application of independent isolation was still low ( 49.5% of those who answered the questionnaire correctly) , the knowledge of women of childbearing age regarding the application of the Covid-19 Protocol at home has reached 78.1% (high) and knowledge of women of childbearing age regarding the application of the Covid-19 Protocol in the workplace has reached 82% (high).Keywords: Covid-19, Self-isolation, Covid-19 protocol